2016
DOI: 10.1080/13696998.2016.1265973
|View full text |Cite
|
Sign up to set email alerts
|

Continuous prophylaxis with recombinant factor IX Fc fusion protein and conventional recombinant factor IX products: comparisons of efficacy and weekly factor consumption

Abstract: Comparisons of clinical study results suggest weekly injections with rFIXFc result in similar bleeding rates and significantly lower weekly factor consumption compared with more-frequently-injected conventional rFIX products. The real-world effectiveness of rFIXFc may be higher based on results from a model of the impact of simulated differences in adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Prophylaxis with long-acting rFIX concentrates has been shown to reduce mean FIX consumption compared with prophylaxis with standard-acting rFIX by almost 50% [84]. Also, in clinical studies with long-acting rFIX concentrates, weekly FIX consumption was considerably lower (~30-50%) than with patients' previous prophylaxis regimens with standard-acting rFIX or pdFIX [34,85].…”
Section: Overcoming Challenges To Prophylaxismentioning
confidence: 98%
“…Prophylaxis with long-acting rFIX concentrates has been shown to reduce mean FIX consumption compared with prophylaxis with standard-acting rFIX by almost 50% [84]. Also, in clinical studies with long-acting rFIX concentrates, weekly FIX consumption was considerably lower (~30-50%) than with patients' previous prophylaxis regimens with standard-acting rFIX or pdFIX [34,85].…”
Section: Overcoming Challenges To Prophylaxismentioning
confidence: 98%
“…85 There is no escape from providing comparative, convincing, robust evidence that the effects of gene therapy are worth its cost. 85 There is no escape from providing comparative, convincing, robust evidence that the effects of gene therapy are worth its cost.…”
Section: Cos T-effec Tivene Ss and He Alth Technology A Ss E Ss Mentmentioning
confidence: 99%
“…70,73,74 For haemophilia, there are established and effective treatments. 85 There are also emerging ones, such as mimetics, recently shown at HTA assessment to be effective, safe and cost-effective, ie, able to reduce societal cost. 86,87 In assessing value, gene therapy will be compared with them.…”
Section: Me a Suring Outcome S In Haemophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…Manco‐Johnson et al 1 were the first to prospectively demonstrate in a randomized study the superiority of prophylaxis over episodic treatment in people with haemophilia. Since and even before this landmark study, the many benefits and values of prophylaxis were demonstrated through multiple prospective and retrospective analyses 2‐11 . In the modern era, prophylaxis is optimized through several approaches, which include varying the dose, varying the dosing frequencies and exploring alternative routes of administration.…”
Section: Introductionmentioning
confidence: 99%